Caracterización y evaluación de la sustentabilidad agropecuaria de treinta familias de la parroquia Mulliquindil del cantón Salcedo, Cotopaxi 2021 - Meneses Espinoza, Michelle Dayana (2021)
This research was carried out in the Salcedo canton in the Mulliquindil parish where its main objective was to characterize and evaluate the agricultural sustainability of thirty families of the Mulliquindil parish of the Salcedo canton of the province of Cotopaxi 2021, where the methodology based on Sarandón, in the characterization it was determined with 57% where the woman is responsible for the administration of the production units, as well as the age that predominates is the one that goes from 41 to 50 years with 46.67% of the producers, in addition there is a low education index with 76.67% of which only have primary education, on the other hand the vast majority of its prevalent crop is corn with 70%, another determined factor is the raising of animals where 46.67% is cattle, as well as in the social aspect we determine that the majority of the producers have their own property titles but their land area that they own for self-consumption is less than 1000m2, making production difficult. In the evaluation of the sustainability of the thirty families, 3 dimensions were determined, where the dimensión. The economic dimension obtained a value of 2.26, the environmental dimension with a value of 2.32, and finally the socio-cultural dimension with a value of 2.32, obtaining a general average of sustainability of 2.33, the same that indicates us that we have a sustainable production system complying with what was expressed by Sarandón